English Intensifiers as Devices of Emotional Enhancement - Asst. Prof. Nada Aziz Yousif AL-Muttalibi (الأستاذ, 2023)
Intensifiers are adverbials or adverbial phrases that are used to enhance the meanings of certain constructions. The study aims to investigate English intensifiers and their functions as devices of emotional enhancement .Moreover; they identify students with this grammatical item. The significance of the research is that intensifiers function as linguistic devices to maximize the meaning or, in a certain sense, intensify the emotional tone of words and expressions. Some commonly used intensifiers include very, too, at all, absolutely, extremely, really, wh-words or expressions, etc. e.g. what on earth are you doing? In terms of their semantic classes, intensifiers can be divided into Amplifiers, Emphasizers and Downtoners. The problem of this research is that the students find it difficult to comprehend the functions of English intensifiers. In terms of the method used in this research, the researcher tries to give a detailed analysis of the most common English intensifiers. An exercise relevant to the topic is adopted to enhance the research. The analysis of the results reveals that the third-year Iraqi college students succeed in operating intensifiers in a way that shows their ability to handle this grammatical item.